If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(6x+9)=-18
We move all terms to the left:
-2(6x+9)-(-18)=0
We add all the numbers together, and all the variables
-2(6x+9)+18=0
We multiply parentheses
-12x-18+18=0
We add all the numbers together, and all the variables
-12x=0
x=0/-12
x=0
| 3g+3.59=16.88 | | (x+9)+(4x-5)+3x=180 | | 6x-6=5x+15 | | -4b+8=-36 | | (3x/8)=12 | | -4(3-7x)=72 | | 4x+5=3x-x+13 | | 10y+9=24 | | 1/3x-1/2=11/3 | | 7(2x+3)=-21 | | 1.25y+y=5 | | 1/3h=6,h=2 | | -6(7x+9)=-138 | | 1/6x-3=4 | | 3/2(x−2)−5=19x | | 32(x−2)−5=19x | | 3(x+2)=(3x-4) | | 7.7-0.5x=4.7 | | 3^(4-x)-7=74 | | 5(4x-1.5x)+12=12=4x-2 | | 25-30x=65+20x | | 16y-6=14 | | 5.45+x=8 | | (3m+1)(-2)=11 | | 3(6x-3)=99 | | 0.7=y/4 | | 2/3=1/3(x-4) | | 4.7=7.7=0.5x | | 2x-5=10x+20 | | 3/5=3/5x+4 | | 6m(m-6)=0 | | 4g+3.72=20.84 |